STRATEGI PEMBELAJARAN LISTENING TEAM DALAM UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR PESERTA DIDIK - Yanuar, Ahmad (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2024)
The purpose of this study is to improve learning activities and to improve learning outcomes by implementing the listening team learning model for students of Class VIIIA on the Material of Faith in the Book of Allah in the Subject of Islamic Religious Education at SMP Negeri 1 Nguntoronadi, Wonogiri Regency in the 2024/2025 Academic Year. This study is a Classroom Action Research (CAR) with the application of the Listening Team learning model on the material of Faith in the Book of Allah SWT in the subject of Islamic Religious Education. This learning model has advantages including being able to develop students' cognitive abilities, make children think critically during the discussion process, make children with interpersonal and intrapersonal abilities develop better. Based on the study, it was obtained that in the first cycle it began to be seen that students' abilities mastered the learning material with an average value of 67.33 with a sufficient level of ability. However, there are still students who are less active, less cooperative, less motivated in learning Islamic Religious Education, especially the material of Faith in the Book of Allah SWT. This is because students' mastery of the material and concentration on the material are still lacking. In cycle II with the same material, it can be seen that the learning outcomes of students have increased, where the average value of student learning outcomes is 80.67 with a level of mastery of learning materials classified as good and above the Learning Objective Criteria Completion. Based on the results obtained, the learning outcomes of students in mastering learning materials have made significant progress.